To B(TA) or not to B(TA)? On the Legality and Desirability of Border Tax Adjustments from a Trade Perspective - Henrik Horn; Petros C. Mavroidis (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
This paper asks two questions concerning Border Tax Adjustments for climate purposes, when viewed from a trade perspective: First, under what conditions are BTAs possible in the WTO-world? To address this issue, the paper provides a detailed discussion of the relevant law and case law. We also apply our main conclusions on what we consider to be paradigmatic cases of measures to address climate change where trade concerns are raised. We conclude that the WTO regime is no major obstacle to those aspiring to use BTAs, although the allocation of the burden of proof could be an issue. The second issue addressed is whether the economic literature on the desirability of BTAs adequately reflects concerns that have been raised in the trade policy community. Here we conclude that it has hardly addressed these concerns at all. We also point to some aspects of BTAs that would be important to take into account in a more complete analysis.
Keywords: Q56; F18; F42; K32; K34; 330